Iron Overload Is Associated With Oxidative Stress and Nutritional Immunity During Viral Infection in Fish - Tarifeño-Saldivia, Estefanía; Aguilar, Andrea; Contreras, David; Mercado, Luis; Morales-Lange, Byron; Márquez, Katherine; Henríquez, Adolfo; Riquelme-Vidal, Camila; Boltana, Sebastian (Frontiers in Immunology, 2018)
Iron is a trace element, essential to support life due to its inherent ability to exchange electrons with a variety of molecules. The use of iron as a cofactor in basic metabolic pathways is essential to both pathogenic microorganisms and their hosts. During evolution, the shared requirement of micro- and macro-organisms for this important nutrient has shaped the pathogen–host relationship. Infectious pancreatic necrosis virus (IPNv), affects salmonids constituting a sanitary problem for this industry as it has an important impact on post-smolt survival. While immune modulation induced by IPNv infection has been widely characterized on Salmo salar, viral impact on iron host metabolism has not yet been elucidated. In the present work, we evaluate short-term effect of IPNv on several infected tissues from Salmo salar. We observed that IPNv displayed high tropism to headkidney, which directly correlates with a rise in oxidative stress and antiviral responses. Transcriptional profiling on headkidney showed a massive modulation of gene expression, from which biological pathways involved with iron metabolism were remarkable. Our findings suggest that IPNv infection increase oxidative stress on headkidney as a consequence of iron overload induced by a massive upregulation of genes involved in iron metabolism